RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma Cacao L.) TERHADAP APLIKASI PUPUK ORGANIK CAIR PADA JENIS AKSESI BUAH KAKAO YANG BERBEDA - Nasamsir Nasamsir (Universitas Batanghari Jambi, 2014)
This study was conducted to assess the response to the cacao seeds organic liquid fertilizer applications (POC) NAP combined with some kind of fruit cacao accessions. The study was conducted in the Pattimura Rt. 38 Recognize Great Edinburgh, starting on May 1, 2014 until July 31 2014 cocoa seedlings were grown in growth media in a polybag. The design environment used in this study was a randomized complete block design (RAK) 4x6 factorial with four replications. POC applications NAP consists of 4 (four) degree, that is; 0 ml / L of water (control), 10 ml / L of water, 20 ml / L of water, and 30 ml / L of water. Factor Type Accession Cocoa (V) consists of 6 (six) level, ie; ¬V1, V2, V3, V4, V5, and V6. The variables used are the RPA response, LTR, and LAB age 14 to 70 days after planting. The results showed no interaction of a combination of the application (POC) NAP with some kind of fruit cacao accessions against RPA, LTR, and LAB age 14 to 70 days after planting. Application of 10 ml per liter of POC NAP accession combined with large red fruit (V3) shows the RPA, LTR, and the highest LAB.Key words ; cocoa seeds, POC NAP, Accession fruit, RPA, LTR, and LAB